(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Botswana stands out among sub-Saharan African nations for its economic and human development. The central aim of this paper is to consider what makes Botswana different. This paper asserts that the attitudes and perceptions of Batswana (i.e., the people of Botswana) contribute to the nation’s economic and human development. It considers how Batswana’s attitudes and perceptions differ from populations in other sub-Saharan African countries and the implications of such differences in explaining what makes Botswana’s economic and human development patterns stand out from other sub-Saharan African nations. This paper’s findings indicate that political attitudes and perceptions of the people in sub-Saharan Africa, such as Botswana, are essential and should not be ignored as factors influencing economic and human development success. Furthermore, it suggests there may be something different about how democracy and governance operate in Botswana that shapes attitudes and perceptions relative to other sub-Saharan African nations.